2009
DOI: 10.1002/jctb.2213
|View full text |Cite
|
Sign up to set email alerts
|

High level of laccases production by Trametes trogii culture on olive mill wastewater‐based media, application in textile dye decolorization

Abstract: BACKGROUND: Laccases are receiving increasing attention as potential industrial enzymes in various applications. Therefore, it is important to find inexpensive and optimized media for large-scale commercial production. The present work aims to valorize olive mill wastewater (OMW) by its use as base media for laccases production by Trametes trogii and use of the laccases produced for decolorizing textile dyes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 37 publications
(32 reference statements)
2
8
0
Order By: Relevance
“…The ability of Trametes trogii to decolorize industrial dyes was confirmed by several studies [5,[9][10][11][12]. Thus, strain T. trogii proved to be an efficient tool for the dye degradations such as Remazol Brilliant Blue R (RBBR) [9], blue solophenyl, blue tubantin GLL 300, black tubantin VSF 600, yellow solophenyl and red BLL [11], Neolane blue, Neolane pink, Neolane yellow, Maxilon blue, Basacryl yellow and Bezaktiv S-BF turquoise [10].…”
Section: Introductionmentioning
confidence: 62%
See 4 more Smart Citations
“…The ability of Trametes trogii to decolorize industrial dyes was confirmed by several studies [5,[9][10][11][12]. Thus, strain T. trogii proved to be an efficient tool for the dye degradations such as Remazol Brilliant Blue R (RBBR) [9], blue solophenyl, blue tubantin GLL 300, black tubantin VSF 600, yellow solophenyl and red BLL [11], Neolane blue, Neolane pink, Neolane yellow, Maxilon blue, Basacryl yellow and Bezaktiv S-BF turquoise [10].…”
Section: Introductionmentioning
confidence: 62%
“…Copper ion was necessary for laccase activity [17]. Previous results obtained, using copper T. trogii laccase inducer, have clearly demonstrated that laccase is seemingly the key enzyme responsible for the efficient decolorization [9][10][11]16]. …”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations